PRODUCTIVITY AND COMPETITIVENESS IN THE PERUVIAN TEXTILE-CONFECTIONERY INDUSTRY 2012-2015 - Arrarte Mera, Raúl Alberto (2017)
The purpose of this paper is to analyze if the textile-clothing sector generated productivity and competitiveness in the period 2012-2015. This was sponsored by the Vice-Rectorate of Research and Graduate Studies of the National University of San Marcos. The research is exploratory, non-experimental descriptive-quantitative, longitudinal type of evolutionary analysis of the sample based on the financial statements of companies registered in the Lima Stock Exchange: Creditex, Michell & Co., and Universal Textil; combined with primary and secondary information. Three ways of solution are proposed: a) To act independently like the Benetton textile company; B) To develop Internal Cooperation; C) To act integrated in the Alliance of the Pacific. It is concluded that productivity and competitiveness have not been generated in the period of study, due to: high logistic costs; reduced exchange rate; tax overhead; low international prices; labor costs and closing of markets by international recession.